Understanding smart cities: a systematic review - Silva, Luan Carlos Santos; Riedo, Ijean Gomes; Mendonça, Jane Correa Alves; Nobre, Luan Batista Oliveira; Maioli, Samanta Fernandes Vieira (Revista de Administração da UFSM, 2024)
Purpose: Smart cities are emerging as a fast-growing scientific research topic; much of the knowledge generated is particularly of a technological nature. The objective of this research was to identify how the articles approach the theme of smart cities from the perspective of innovation and technology. Design/methodology/approach: The methodological procedure consisted of a systematic review of the literature; the process was carried out in three main stages: planning, reviewing, and reporting/disclosure. The period established for searches was from 2006 to 2021, using the databases: Emerald Insight, Scielo, Scopus, and Web of Science, and the Mendeley tool was used to filter articles within the theme. Findings: After careful selection, 349 studies were found, based on the objective and relevance of this research. Regarding the databases, Emerald Insight presents 91 articles, Web of Science 83 articles, Scopus 101 articles, and Scielo 74 articles. About publications per country, Italy presents 12 articles, the United Kingdom 11 articles, and Spain and the United States 8 articles each. Information and Communication Technology (ICT) has great potential to improve the quality of life of the population living in smart cities, innovation has always been significant to competitiveness and is vital to smart cities and tourist destinations. The sustainable and smart development of cities should be developed based on specific principles: synergy, creativity, and circularization. Originality/value: The research is considered relevant since the theme of Smart cities in innovation and management is relatively new in the scientific area. It is opportune that governments and citizens discuss what they want for the future of their cities, understanding how technology can be an exceptional issue among nations around the world. A unique model of a smart nation can emerge and boost cities over the next 50 years.